Laser Management of Glaucoma in Exfoliation Syndrome. Issue 7 (July 2018) - Sandhu, Simrenjeet; Damji, Karim F.
Abstract : Argon laser trabeculoplasty as well as selective laser trabeculoplasty can be used in patients with exfoliation syndrome with similar safety and efficacy. However, treatment effect may abruptly reverse and patients need to be followed regularly to monitor intraocular pressure control. Newer laser treatment modalities including micropulse laser trabeculoplasty, titanium sapphire laser trabeculoplasty and pattern scanning trabeculoplasty show promising results but need to be studied in exfoliation patients. For exfoliation patients with angle closure, peripheral iridectomy, iridoplasty or cataract extraction can be very helpful. For refractory exfoliation glaucoma, transscleral diode laser cyclophotocoagulation offers a reasonable option to lower intraocular pressure. Other approaches to cyclophotocoagulation such as micropulse transcleral diode laser need to be studied further in exfoliation patients.